Peran Strategis Manajemen Keuangan Dalam Meningkatkan Profitabilitas Dan Kinerja Bisnis Syariah - M. Nashrullah; Ahmad Fatan Al Banna; Agus Eko Sujianto; Amalia Nuril Hidayati (JOURNAL OF SHARIA ECONOMICS, 2026)
Sharia financial management is a financial management system based on the principles of the Qur'an and Hadith, emphasizing transparency, fairness, and accountability in business activities. This study aims to analyze the role of Sharia financial management in improving the profitability and performance of Sharia-based businesses in Indonesia. The research method uses a qualitative approach through library research, reviewing various scientific literature, books, journals, and relevant previous research. The results show that the effective implementation of Sharia financial management can optimize cash flow, minimize financial risk, and increase company stability in facing global economic dynamics. Furthermore, the application of non-usury principles and measured fund management can increase investor confidence and consumer loyalty. Thus, Sharia financial management is an important strategy for increasing competitiveness, business sustainability, and sustainable economic prosperity.